"Is It Safe?": The Many Unanswered Questions about Medications and Breast-feeding. Issue 3 (September 2019) - Byrne, J.J.; Spong, C.Y.
Abstract : ( N Engl J Med . 2019;380(14):1296–1297. Doi:10.1056/NEJMp1817420) While an estimated 83% of mothers in the United States breastfeed, and more than half of mothers worldwide take medication in the postpartum period, there has been a lack of clinical studies examining the effects of drugs on breastfeeding mothers and children. In 2006, LactMed, an online database from the National Library of Medicine, published information on the levels of 1408 drugs in breast milk and infant blood and the effects of these drugs on lactation. However, the recommendations for more than half of those drugs were not based on lactation-specific data as of November 2018 and very few (2%) were based on strong data.